Hip Reconstruction Osteotomy by Ilizarov Method as a Salvage Option for Abnormal Hip Joints. (6th May 2014) - Umer, Masood; Rashid, Haroon; Umer, Hafiz Muhammad; Raza, Hasnain
Abstract : Hip joint instability can be secondary to congenital hip pathologies like developmental dysplasia (DDH) or acquired such as sequel of infective or neoplastic process. An unstable hip is usually associated with loss of bone from the proximal femur, proximal migration of the femur, lower-extremity length discrepancy, abnormal gait, and pain. In this case series of 37 patients coming to our institution between May 2005 and December 2011, we report our results in treatment of unstable hip joint by hip reconstruction osteotomy using the Ilizarov method and apparatus. This includes an acute valgus and extension osteotomy of the proximal femur combined with gradual varus and distraction (if required) for realignment and lengthening at a second, more distal, femoral osteotomy. 18 males and 19 females participated in the study. There were 17 patients with DDH, 12 with sequelae of septic arthritis, 2 with tuberculous arthritis, 4 with posttraumatic arthritis, and 2 with focal proximal femoral deficiency. Outcomes were evaluated by using Harris Hip Scoring system. At the mean follow-up of 37 months, Harris Hip Score had significantly improved in all patients. To conclude, illizarov hip reconstruction can successfully improve Trendelenburg's gait. It supports the pelvis and simultaneously restores knee alignment and corrects lower-extremity length discrepancy (LLD).